Reformasi Perserikatan Bangsa-Bangsa (Beberapa Usaha Indonesia) - Suny, Ismail (Indonesian Journal of International Law, 2004)
United Nations, as the biggest international organization, is in the middle of doing internal reformation regarding the structure enlargement of the Security Council. Indonesia, as the biggest moderate Moslem country in the world is proposed itself to be seated as one of the permanent member of the Security Council. It is expected that this movement will influence the development of international law either directly or indirectly. This article contains a discussion about the writer’s experiences during his appointments as the representative of Indonesian government in several experiences during his appointments as the representative of Indonesian government in several international conferences concering human rights and use of the rule of law to keep the world peace and secuity. The discussion has given a better picture of strong background of the Indonesian role and participation in peace keeping and in guarding the world law order.